Preliminary Attempt to Predict Risk of Invasive Pulmonary Aspergillosis in Patients with Influenza: Decision Trees May Help? - Valeria Bellelli; Guido Siccardi; Livia Conte; Luigi Celani; Elena Congeduti; Cristian Borrazzo; Letizia Santinelli; Giuseppe Pietro Innocenti; Claudia Pinacchio; Giancarlo Ceccarelli; Mario Venditti; Gabriella d'Ettorre (MDPI AG, 2020)
Invasive pulmonary aspergillosis (IPA) is typically considered a disease of immunocompromised patients, but, recently, many cases have been reported in patients without typical risk factors. The aim of our study is to develop a risk predictive model for IPA through machine learning techniques (decision trees) in patients with influenza. We conducted a retrospective observational study analyzing data regarding patients diagnosed with influenza hospitalized at the University Hospital "Umberto I" of Rome during the 2018-2019 season. We collected five IPA cases out of 77 influenza patients. Although the small sample size is a limit, the most vulnerable patients among the influenza-infected population seem to be those with evidence of lymphocytopenia and those that received corticosteroid therapy.